Formulation of Aromatherapy Candles from Agarwood (Aquilaria malaccensis) Leaf Extract as a Product Innovation and an Entrepreneurship Opportunity - Nolensah Sinaga; Agus Susanti (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2026)
Aromatherapy is the use of essential oils derived from natural materials to improve physical and psychological well-being. One of the most popular aromatherapy products is the aromatherapy candle, which provides relaxation while creating a comfortable atmosphere. This study aimed to develop aromatherapy candles based on agarwood (Aquilaria malaccensis) leaf extract, evaluate product quality, analyze public acceptance, and identify their potential as an entrepreneurial opportunity. This study employed an experimental method with a descriptive approach. The research stages included the extraction of agarwood leaves through a distillation process, the formulation of aromatherapy candles, product validation by three experts using sensory evaluation, and a public acceptance test involving 40 respondents using a Likert-scale questionnaire. The results showed that the third experiment produced the best extract characteristics, including a golden-yellow color, a stronger distinctive agarwood aroma, and an oily texture. The public acceptance test indicated that the average scores for color, texture, ease of use, and aroma were 3.16, 2.90, 3.42, and 3.02, respectively, which were categorized as good to very good. These findings demonstrate that agarwood leaf extract has the potential to be used as an alternative ingredient in the production of aromatherapy candles, in addition to receiving a high level of public acceptance, the product possesses economic value and can be developed as an innovative product and entrepreneurial opportunity in the beauty, spa, wellness, and creative industries.